Ethnobotanical Study of Cilokaq, Traditional Musical Art of Sasak Tribe on Lombok Island - Sahid Imam Wahyudi; Sukiman Sukiman; Kurniasih Sukenti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Cilokaq is a traditional musical art of Sasak Tribe, which features several verses of songs with instruments such as gongs, drums, flutes, and gambus. The making of Cilokaq musical instrument uses plants that are obtained from nature, and this plant utilization should be well documented in order to assure the preservation of cultural heritage and also the plant resources contained in it. The purpose of this research is to identify the species of plants used in t Cilokaq musical instruments and to explore aspects of plant utilization and other ethnobotanical aspects of Cilokaq on Lombok Island. This research used qualitative and quantitative data collected through observations, interviews, documentation, and literatures study. Index of Cultural Significance (ICS) value was used to predict the importance value of each species involved in Cilokaq instruments. Informants were determined using snowball sampling technique. As a result, there were eight plants species categorized in 5 families used in making Cilokaq instruments, while there were 6 species belongs to 5 families used as offerings (andang-andang). Rotan (Calamus sp.) had the highest value of ICS (80), while Areca catechu, Gossypium herbaceum, Oryza sativa, Capsicum annuum, and Piper betle had the lowest value (8). Plants such as Ficus fistulosa, Calamus sp., and Schizotachyum blumei are species that begin to be difficult to find so that conservation action are needed in order to preserve the Cilokaq traditional art and plants species involved in it.